szyszunia220

rozwiąż równanie: a) (x-1)^2+(x-2)^2-(x-4)=100 b) 2(2x-7)-6x=66-3(3x+1)

+0 pkt.
Odpowiedz

1 answer

about 14 years ago

a) (x-1)^2+(x-2)^2-(x-4)=100 x^2-2x+1+x^2-4x+4-x+4-100=0 2x^2-7x-91=0 ∆= 7^2-4*2*(-91) = 49-(-728) = 777 x1= -(-7)-\sqrt{777}\over2*2 x1= 7-28\over4 x1=-5,25 x2= -(-7)+\sqrt{777}\over2*2 x2= 7+28\over4 x2=8,75 b) [mat]2(2x-7)-6x=66-3(3x+1) 4x-14-6x=66-9x-1 -2x+9x=65+14 7x=79 x=11,3

zuzzi

Beginner Odpowiedzi: 32 0 people got help

Najnowsze pytania w kategorii Matematyka

Ładuj więcej